COVID-19 and its current trends with long term implication - Mahadik, A. (Psychology and Education, 2021)
BACKGROUND: The coronavirus disease 2019 or COVID-19 is a serious medical threat that is posed before since more than a year. Scientists and researchers from all over the world are working on the solution on the ongoing problem. SUMMARY: The mutated strain of the novel coronavirus has been successful in creating a buzz around the circuit of concerned people. The COVID-19 is being uncertain throughout its stay and any prediction would possibly go wrong. Long term implications may lacksome major study but many lessons and parallels can be drawn from the previous similar outbreaks of SARS and MERS. CONCLUSION. More fact based along with broad based study is needed to understand and correlate the COVID-19 andits long-termimplications.